math middle school

## Answer

**answer 1**

answer:

6:45

If you must leave 45 minutes before the 7:30 start, please step-by-step explain when you must leave

## Related questions

When Sally tossed the water balloon into the air, the water balloon was 5 feet off the ground. Use the quadratic equation 0 = -t^2 + 4t + 5 to calculate the time t it takes for the water balloon to hit the ground.

### Answer

answer:

Step by step explanation:

have

Solve a quadratic equation to find the zero or x-intercept

please remember

x-intercept is the value of x when the value of y is equal to 0 (the water balloon hits the ground)

we know

The formula for solving a quadratic equation of the form equals

In this problem we have

so

Into the formula

so

the solution is

answer:

5 seconds

Step by step explanation:

ttm/imagine math

Ana is a competitive runner. You want to improve your performance and decide to track your stats for six months to determine if or when you run is affecting your performance. Your worksheet contains the following data: start and end times, total time, and distance. Three months later, Ana wants to know the average distance she has run. How should you calculate the average distance? arrive. Enter the text =av in the cell from the end of the data; then select the AVERAGE function from the list of autocomplete formulas, and enter the function parameters. C. Enter the text =function in the cell from the end of the data; then select the AVERAGE function from the automatic function list, and then enter the parameters of the function. b. Enter the text =ms in the cell from the end of the data; then select the MAX function from the list of autocomplete formulas, and enter the function parameters. d. Enter the text =su at the end of the data in the Distance column; then select the SUM function from the selection function list, and then enter the parameters of the function.

### Answer

answer:

Uh-huh

Step by step explanation:

Question 6 (multiple choice, worth 5 points) (8.05 HC) presents student work to solve a set of equations: Equation A: y = 15 − 2z Equation B: 2y = 3 − 4z Step 1: −2 (y ) = −2(15 − 2z) [Equation A multiplied by −2. ] 2y = 3 − 4z [Equation B] Step 2: −2y = 15 − 2z [Simplify Equation A from Step 1. ] 2y = 3 − 4z [Equation B] Step 3: 0 = 18 − 6z [Add equation from Step 2. ] Step 4: 6z = 18 Step 5: z = 3 At which step did the student make the first mistake? Step 1 Step 2 Step 3 Step 4

### Answer

answer:

- The student first made a mistake in the second problem because he did not apply the assignment property correctly.

explain:

Here, I replicate each step taken and review them algebraically until I find the first mistake the student made.

0) Start: System of equations:

- Equation A: y = 15 − 2z

- Equation B: 2y = 3 − 4z

1) Step 1:

−2(y) = −2(15 − 2z) [equation A multiplied by −2. ]

2y = 3 − 4z [equation B]

This process is algebraically correct because the student correctly uses the multiplicative property of the equation: both sides of equation A are multiplied by the same number 2.

However, Equation B is not an algebraic operation.

2) Step 2:

- −2y = 15 − 2z [Equation A from Step 1 has been simplified. ]

- 2y = 3 − 4z [equation B]

This process is algebraically wrong because the student misuses the distributive property of multiplication to simplify equation A:

- −2(y) = −2(15 − 2z)

- Incorrect: -2y = 15 - 2z,

- The error was that the student did not multiply -2 by 15 and -2 by -2z

- The correct procedure is:

-2y = -2(15) - 2( - 2z)

-2y = -30 + 4z

Conclusion: The student made a mistake in the second question because he did not apply the assignment attribute correctly.

answer:

second step

Step by step explanation:

Because the distribution is not good.

John rolls a pair of six-sided number cubes. What is the probability that the sum of the numbers on the number cube is a multiple of 3 or odd?

a 1/2

B 2/3

C 1/6

3/4

### Answer

answer:

B 2/3

Step by step explanation:

When you roll two dice, there are a total of 36 possible outcomes.

You need to find the number of results whose sum is a multiple of 3. Then you need to find the number of results that sum to an odd number. Add the two numbers and divide by 36.

Here are all the outcomes of rolling two dice. Each result that sums to a multiple of 3 is shown in bold. Each odd result is shown in italics. Some results are multiples of 3 and odd numbers.

11 12 13 14 15 16

21 22 23 24 25 26

31 32 33 34 35 36

41 42 43 44 45 46

51 52 53 54 55 56

61 62 63 64 65 66

We are interested in multiples of 3 or odd numbers or any result of multiples of 3 and odd numbers.

We count the number of results in bold, italic, or bold and italic.

The total is 24.

p (multiple of 3 or odd) = 24/26 = 2/3

Answer: B. 2/3

Step by step explanation:

Some results are multiples of 3 and odd numbers.

11 12 13 14 15 16 21 22 23 24 25 26 31 32 33 34 35 36 41 42 43 44 45 46 51 52 53 54 55 56 61 62 63 64 65 66

We count the number of results in bold, italic, or bold and italic. The total is 24.

p (multiple of 3 or odd) = 24/26 = 2/3

Jess made a 3 1/2 batch of oatmeal cookies with 11 1/2 cups of flour. Makes 24 cookies in one batch. How many batches of cookies can she make in 16 1/2 if she follows the same recipe?

### Answer

Jess made a 17/2 o batch of oatmeal cookies with a few cups of flour.

What is an incorrect score?

An incorrect fraction is one in which the numerator is greater than or equal to the denominator.

With that in mind, Jess makes batches of oatmeal cookies with just a few cups of flour.

One batch makes 24 cookies.

To find how many cookie batches you can make:

First, convert the mixed fractions to improper fractions.

= 23/2

= 7/2

= 33/2

Leave n batches of cookies that you can make with 3 3/2 cups of flour.

We can write,

+subway=

Meter = 33/2 - 23/2

Subway = 10/2

Metro = 5

this means,

If Jess made a batch of oatmeal cookies with a few cups of flour.

So Jess uses + 5 cups of flour to make + 5 batches of oatmeal cookies.

Jess made a 17/2 batch of oatmeal cookies with a few cups of flour.

So you can make 17/2 or more batches of cookies.

Learn more about Improper Fractions;

brainly.com/question/21449807

#SPJ5

Answer: Jesse can make 8 1/2 batches of cookies.

Step by step explanation:

Since you're only adding 5 more cups (11 1/2 to 16 1/2) to the recipe, just add 5 to 3 1/2 (5+ 3 1/2)

F(x)=x−7 g(x)=4x^3

What is f(x)+g(x)?

f(x)+g(x)=x+x

f(x)+g(x)=4x^3+x−7

f(x)+g(x)=−4x^3−x+7

f(x)+g(x)=4x^3+x

### Answer

answer:

f(x)+g(x)=4x^3+x−7

Step by step explanation:

To find f(x) + g(x), add expressions by combining similar terms. Remember that similar terms are terms with the same base and exponent.

f(x) + g(x) = x - 7 + 4x^3

f(x) + g(x) = 4x^3 + x -7

Si f(x)=−x^2−8x+7, y g(x)=x−1, ¿a qué equivale (g−f)(x)? (g−f)(x)=−x^2−7x+6

(g−f)(x)=x^2+9x−8

(g−f)(x)=−x^2−9x+8

(g−f)(x)=−8x+8

### Answer

answer:

(gf)(x) = x^2 + 9x - 8

Step by step explanation:

To find the expression (g-f)(x), subtract the two expressions from each other by assigning a negative number in f(x) and combining similar terms.

(gf)(x) = x-1 -(-x^2 - 8x + 7)

(gf)(x) = x - 1 + x^2 + 8x -7

(gf)(x) = x^2 + 9x - 8

Find g^−1 (x) when g(x) = 3/5 x −9.

5/3x - 1/9

5/3 x + 9

−3/5 x+ 9

5/3 x + 15

### Answer

answer:

5/3 x + 15

Step by step explanation:

The inverse of a function is the reflection in the line y = x. So it can be found algebraically by swapping y and x in the equation and separating to solve for y.

g(x) = 3/5 x - 9

x = 3/5 y - 9

x + 9 = 3/5 y

5(x+9) = 3y

(5x + 45)/3 = y

5/3x + 15 = y

F(x)=x^3+4x−7 g(x)=6x^4−5x+2

What is f(x)−g(x)?

f(x)−g(x)=x−x

f(x)−g(x)=−6x^4+x^3+9x−9

f(x)−g(x)=6x^4−x^3−9x+9

f(x)−g(x)=6x^4+x^3−x

### Answer

answer:

f(x)−g(x)=−6x^4+x^3+9x−9

Step by step explanation:

To find f(x) - g(x), subtract the expression by assigning a negative number in g(x), then combine similar terms. Remember that similar terms are terms with the same base and the same exponent.

f(x) - g(x) = x^3 + 4x - 7 -(6x^4 - 5x + 2)

f(x) - g(x) = x^3 + 4x - 7 -6x^4 + 5x - 2

f(x) - g(x) = -6x^4 + x^3 + 9x - 9

4. Solve the given system using the substitution method.

y = 4x – 6

8x – 2y = 14

A。

(14, 12)

B.

(12, 14)

C。

There are countless solutions.

D.

There is no solution.

3.

Solve a given system using substitution methods.

y = 3x – 7

6x – 2y = 12

A。

There is no solution.

B.

(12, 14)

C。

(14, 12)

D.

There are countless solutions.

5.

To solve, use the substitution method.

y + 2x = 7

14 – 4x = 2y

A。

The solution is (1, 5)

B.

The solution is (21, 0)

C。

There are countless solutions.

D.

There is no solution.

### Answer

answer:

4. No solution

Step by step explanation:

To solve a system of equations, find a solution (x, y) that satisfies both equations. One method that can be used is substitution. It is done by substituting one function into another and simplifying.

Substitute y = 4x - 6 into 8x - 2y = 14.

8x - 2(4x - 6) = 14

8x - 8x + 12 = 14

12 = 14 errors

Since the variable was removed, false declarations were found, so there is no solution for this system.

Solve 3 and 5 in a similar fashion. If the variables are eliminated again and the true proposition is found, then the solution is infinity. If the variable was not eliminated, substitute it back into the equation to find the other.

Patty went swimming for 1 hour and 15 minutes on Monday. On Tuesday he swam twice as much as on Monday. On Wednesday he swam 50 minutes less than Tuesday. During those three days, how much time did you spend swimming?

### Answer

answer:

He spent 5 hours and 25 minutes swimming.

Step by step explanation:

She spent:

Monday 1 hour 15 minutes

Tuesday 2 hours 30 minutes

1 hour and 40 minutes is Wednesday

(all added up)

If f(x)=2x−3 and g(x)=4x+5, what is (f⋅g)(x)? (f⋅g)(x)=8x^2−2x−15

(f⋅g)(x)=6x+2

(f⋅g)(x)=8x^2+22x−15

(f⋅g)(x)=8x−15

### Answer

answer:

(f⋅g)(x)=8x^2−2x−15

Step by step explanation:

To find the expression (f*g)(x), multiply f(x) by g(x) using the distribution properties.

(f*g)(x) = (2x - 3)(4x + 5) = 8x² - 12x + 10x - 15 = 8x² - 2x - 15

The population and area of the four states are shown. Which statement is true about these four states? The states with the least population have the highest population density. The second least populous state has the lowest population density. The least populous state has the lowest population density. The second most populous state has the lowest population density.

### Answer

The correct statement for the given option is The state with the second lowest population has the lowest population density.

What is a relationship?

Ratio tells us how many times one number contains another number.

A state's population density is the ratio of the state's population to the state's area. Therefore, the population density of each state can be written as,

Therefore, the correct statement for the given option is The state with the second lowest population has the lowest population density.

Learn more about scale:

brainly.com/question/1504221

The second least populous state has the lowest population density.

August organized two dinner parties for his friends. There were 20 guests at the first party and 33 guests at the second party. What is the percentage increase in guest count from first party to second party?

### Answer

answer:

50%

Step by step explanation:

You plan to invest $500 compounded at 12% per year. How much money will you have in 10, 20 and 30 years?

### Answer

question

If you put $500 into a compounding account earning 12% annual interest, how much money will be in the account in 10 years?

result

The amount is $1552.92 and the interest is $1052.92.

question

If you put $500 into an account compounding 12% a year, how much money will be in the account in 20 years?

result

The amount is $4823.15 and the interest is $4323.15.

question

If you put $500 into a compounding account earning 12% annual interest, how much money will be in the account in 30 years?

result

The amount is $14979.96 and the interest is $14479.96.

When fully factored, 3x2−48 equals -

### Answer

answer:

Step by step explanation:

If you're asking what 3x2-48 is, the rules of Pemdas are relevant here.

First, we multiply. So 3 times 2 equals 6.

So 6-48 is -42

If f(x)=(x−3)2+1, what is f(6)?

### Answer

answer:

7

Step by step explanation:

If 6 is x, then it is (6-3)2+1. 6-3 is 3, 3 multiplied by 2 is 6, 6+1=7

The answer is 7...substitute 6 into x and solve

What is the product of 5.86 × 10–7 and 3.1 × 104 What is the value of n in scientific notation for the product?

### Answer

The answer is -2, on the verge of nothing

answer:

-2

Step by step explanation:

2020 prrrrrrrrrr

Cube blocks packed in a cube-shaped storage container The length of the edge of the storage container is 2 1/2 feet the length of the edge of each block 1/5 the length of the edge of the storage container What is the volume of a storage cube? jam

### Answer

answer:

cubic feet

Step by step explanation:

The side lengths of the cube are 1/5 and 1/2 of 2. let's do it:

Therefore, the side length of the cube = 1/2 foot.

The volume of a cube is given by V = x^3, where x is the length of the sides. We know that the length of the side is 1/2, so we have:

Can anyone tell me what is the geometric sequence of 250,100,40,16? ! !

I'll mark the smartest as the best answer!

### Answer

answer:

Step by step explanation:

Step 1. Calculate the common ratio

₁ = 250

a2 = 100

₃ = 40

₄ = 16

Common reasons are

a₃/a2 = 40/100 = 0.4

Step 2. Write the formula for the series

The formula for the nth term of the geometric sequence is

aₙ = a₁rⁿ⁻¹

Therefore, the series formula is